Wood defects / Nor Fadzillah Abu Bakar - Abu Bakar, Nor Fadzillah (2004)
Wood is the basic raw material used to produce many products especially sawn timber. As we know, the good wood can give the best quality to the product, which we produced. Sometimes, the wood defects can give big problem to the all-wood product producer because this wood defects sometimes can be prevented and sometime not. The type of wood defects that we face with is natural wood defects, seasoning wood defects and wood defects during machining. So, the best way to get the quality wood is to control dry it using special drying schedule and to person who handle the machine should be more careful. It is very importance to get the high value of wood in the market. It is because, not easy to get the good log in the short time.